THE ROLE OF TESTIMONY AND TESTIMONIAL ANALYSIS IN HUMAN RIGHTS ADVOCACY AND RESEARCH. (1st October 2012) - Patel, Ian
Abstract : This article addresses the prominence of testimony evidence in the practice and theory of human rights. It examines the use of testimony in legal mechanisms, by international advocacy organizations, and in academic human rights research. It reflects on the reasons behind the prominence of testimony, treating it as a source of evidence, an advocacy tool, and a trope within human rights discourse. This article places testimony in political context, and explores the political implications of the fact that the narrative accounts of victims of state crime are utilized by international advocates/experts as a primary source of evidence. As an original theoretical discussion, this article critiques what it perceives to be the dominant epistemology of testimony in a human rights context. It concludes that the meaning and uses of testimony in a human rights context are curated by international experts, a trend that risks the disenfranchisement of witnesses from the meaning and uses to which their testimony is assigned.